2015
DOI: 10.3991/ijet.v10i4.4518
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Web Accessibility of Educational Websites

Abstract: Abstract-Web accessibility concerns of building websites that are accessible by all people regardless of their ability or disability. The W3C Web Accessibility Initiative (WAI) has been established to raise awareness of universal access. WAI develops guidelines which can help to ensure that Web pages are widely accessible. Assistive technology is used to increase, improve, and maintain capabilities of disabled persons to execute tasks that are sometimes difficult or impossible to do without technical aid. Also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 10 publications
3
22
1
1
Order By: Relevance
“…Overall, the results provide evidence that the level of compliance with respect to web accessibility requirements is relatively very low amongst the public universities in Malaysia. The results seem consistent with what has been reported by similar studies worldwide such as in the Middle East countries (Shawar, 2015), Nigeria (Adepoju & shehu, 2014), Argentina (Laitano, 2015) and Malaysia (Abdul Latif & Masrek, 2010;Abdul Aziz et al, 2010;Abuaddous et al, 2013). AChecker classifies accessibility-related problems into three categories.…”
Section: Web Accessibility Results Based On Acheckersupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, the results provide evidence that the level of compliance with respect to web accessibility requirements is relatively very low amongst the public universities in Malaysia. The results seem consistent with what has been reported by similar studies worldwide such as in the Middle East countries (Shawar, 2015), Nigeria (Adepoju & shehu, 2014), Argentina (Laitano, 2015) and Malaysia (Abdul Latif & Masrek, 2010;Abdul Aziz et al, 2010;Abuaddous et al, 2013). AChecker classifies accessibility-related problems into three categories.…”
Section: Web Accessibility Results Based On Acheckersupporting
confidence: 92%
“…(2015) who diagnosed Argentine public universities, websites based on WCAG 2.0 guidelines indicated serious accessibility issues for most parts of the websites, particularly on the syntax, presentation of the web content and non-text content, and visual readability of the text. Finally, a cross-countries study on selected higher education institutions in the Middle East and England concluded that website accessibility in developed countries was better off than the developing economies (Shawar, 2015).…”
Section: Automated Tools For Web Accessibilitymentioning
confidence: 99%
“…The methodology was combined using a web accessibility evaluation tool and manual analysis carried out by an evaluator [ 38 , 39 ]. The tool used for accessibility evaluation was the Wave tool [ 40 ], developed by the WebAIM organisation. The website accessibility conformity assessment methodology (WCAG-EM) was used, which is considered in the Web Content Accessibility Guidelines 1.0 but is applicable to WCAG 2.1 [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Curl and Browsers (2009) examined web site accessibility over a five year period between 2003 and 2008.They examined 45 universities to compare the result of the different time periods and found that web site accessibility was improved after five years in general and yet, 75.6% of the web sites had errors and did not meet web content accessibility guidelines. Kurt (2011) and Shawar (2015) focused on delving into their own countries' web accessibility issues. Kurt (2011) examined the website accessibility of university for people with visually impaired in Turkey.…”
Section: Review Of University Accessibility Studiesmentioning
confidence: 99%